Intermarriage and Immigrant Employment: The Role of Networks - Delia Furtado; Nikolaos Theodoropoulos (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2009)
The social integration of immigrants is believed to be an important determinant of immigrants' labor market outcomes. Using 2000 U.S. Census data, we examine how and why marriage to a native, one measure of social assimilation, affects immigrant employment rates. We show that even when controlling for a variety of human capital and assimilation measures, marriage to a native increases the probability that an immigrant is employed. An instrumental variables approach which exploits variation in marriage market conditions suggests that the relationship between marriage decisions and employment rates is not likely to arise from positive selection into marrying a native. We then present several pieces of evidence suggesting that networks obtained through marriage play an important part in explaining this effect.
Keywords: J61; J12; J21; 330; Immigration; Marriage; Employment; Networks